2018
DOI: 10.3389/fpsyg.2018.00429
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Appearance Standards and Risk Factors for Eating Disorders in Adolescents and Women of Various Ages

Abstract: The main aim of the present study was to verify the level of impact of sociocultural appearance standards (passive awareness and active internalization) have on body dissatisfaction, the desire to engage in a relentless pursuit of thinness, the adoption of a perfectionistic attitude toward the body, and the development of a tendency to engage in bulimic eating behavior, which can develop in adolescent girls and women of varying ages. The study group comprised 234 individuals: 95 secondary school girls, 33 high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 57 publications
2
55
0
7
Order By: Relevance
“…These data are consistent with the results of other studies conducted on various populations and nationalities, which indicate the increasing epidemiology of eating disorders around the world [1,19]. The results also confirm the significant role of socio-cultural predictors in the development of body dissatisfaction, which is one of the risk factors of eating disorders [2,39,70,78,85,86]. The results show that the significant predictors of variables such as Body Dissatisfaction and bulimic tendencies (Bulimia) for Japanese women were Emotional Dysregulation and Interoceptive Deficits-the former describes affective difficulties involving emotional dysregulation, such as emotional instability and impulsiveness, while the latter is related to disorientation and difficulties with identification and differentiation of emotional states and bodily sensations.…”
Section: Predictors Of Eating Disorders Among the Studied Groups Of Psupporting
confidence: 91%
See 2 more Smart Citations
“…These data are consistent with the results of other studies conducted on various populations and nationalities, which indicate the increasing epidemiology of eating disorders around the world [1,19]. The results also confirm the significant role of socio-cultural predictors in the development of body dissatisfaction, which is one of the risk factors of eating disorders [2,39,70,78,85,86]. The results show that the significant predictors of variables such as Body Dissatisfaction and bulimic tendencies (Bulimia) for Japanese women were Emotional Dysregulation and Interoceptive Deficits-the former describes affective difficulties involving emotional dysregulation, such as emotional instability and impulsiveness, while the latter is related to disorientation and difficulties with identification and differentiation of emotional states and bodily sensations.…”
Section: Predictors Of Eating Disorders Among the Studied Groups Of Psupporting
confidence: 91%
“…The results show the presence of the same correlation in both groups: The higher the Drive for Thinness, the greater the global internalization. This confirms the impact of Western culture which promotes the "cult of thinness" in both populations of young Polish [78] and Japanese women [25,77].…”
Section: Predictors Of Eating Disorders Among the Studied Groups Of Psupporting
confidence: 72%
See 1 more Smart Citation
“…That is, adolescents going through rapid physical changes rely more easily on others' evaluation of their body and appearance than on their own and, therefore, they are highly sensitive to the body image required by society. Indeed, a number of previous studies reported that the tripartite influence of media, family, and peers, and comparison with others enforce adolescents' internalization of the thin-body ideal and increase their body dissatisfaction [2][3][4][5]. A previous study comparing US and Korean middle school students found that Korean girls reported greater body dissatisfaction than US girls [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the socioeconomic index as a predictor of eating disorders, one of the predominant characteristics of these disorders is that they generally occur in patients of a medium-high socioeconomic level [29]. However, it should be considered that socioeconomic levels could be modulated by the socio-cultural standards of appearance, which seem to be not universal [29].…”
Section: Discussionmentioning
confidence: 99%